Intensification Functions of Phrasemes with the Base Words čert ‘devil’, král ‘king’, and drak ‘dragon’ - Křivancová, Michaela (Bohemistyka, 2019)
This contribution focuses on phrasemes with an intensification function. The emphasis is laid on phrasemes with the so-called base word čert ‘devil’, král ‘king’, and drak ‘dragon’. We will attempt to show that the bearer of an intensification function is in some phrasemes the base word itself and in other cases the whole proposition. On several illustrative examples we will prove different formal types of phraseological units which perform an intensification function with the given base words. Furthermore, we will attempt to show that an identical or similar form of phraseological units differing only in the base word (although from one thematic unit) need not have an identical or similar semantic-functional structure.